Effects of Sexual Education Skills on the Treatment Outcomes of Infertile Women - Khodamorad Momeni; Nasrin Jalilian; Kamran Yazdanbakhsh; Zahra Mokari; Mansour Rezaei (Mashhad University of Medical Sciences, 2018)
Introduction: Sexual function disorders in infertile women may indirectly decrease the success rate of their treatment. Therefore, it is essential to eliminate such disorders in order to improve infertility treatment outcomes in women. Considering the lack of research on infertile women, the present study aimed to investigate the effects of sexual education skills on the outcome of infertility treatment in women. Methods: This clinical trial was conducted on 20 infertile women with sextual function disorders aged 22-36 years, who referred to Motazedi Sterility Clinic in Kermanshah, Iran in 2016. Research units were selected via convenience sampling. Subjects were randomly divided into two groups of intervention and control group (10 women in each group). Women in the intervention group received training on sexual education skills (10 sessions), and the control group had no intervention. Data were collected using the sexual function index by Rosen et al. (2000). Data analysis was performed in SPSS version 19 using the Kolmogorov-Smirnov test, Mann-Whitney U test, paired t-test, and Fisher's exact test. Results: Sexual skill training improved the sexual function of infertile women (P=0.001). After three months, the number of pregnancies in the intervention group was higher compared to the control group although the difference was not statistically significant (P=0.291). Conclusion: According to the results, sexual education skills could improve the sexual function of the infertile women. Therefore, it is recommended that sexual skill training be implemented as an effective cognitive-behavioral, non-pharmacological method to enhance sexual and reproductive health.